Perancangan Kursi Pilot Helicopter Jenis Sykorski S-76 Berdasarkan Pendekatan Ergonomik - Sulistyadi, Kohar (JURNAL GAUNG INFORMATIKA, 2013)
Anthropometric measurements of the dimensions is the study of the human body. Anthropometric measurement difficulties caused by several factors: a) the size of the human body is very diverse and depend on age, gender, ethnicity, so some group work often demands certain requirements.Objective article focuses on the effort to design chairs Helicopter pilots Sykorski type S-76 based on the concept and principles of ergonomics.Some of the data required for the design work is based on the principle of the pilot seat with ergonomic support anthropometric data, among others, namely: DataWidth backrest (LS), High backrest (TS), Wide Hips (LP), High Popliteal (TPL), popliteal Ass (PPL) which is supported by data size adult Indonesia (Central Jakarta Usahid student anthropometric data).After the direct measurement data processing based on uniformity test data. Uniformity test is intended to homogenize the data in an Upper Control Limit (UCL)and Lower Control Limit (LCL). Once all the data is uniform, followed by testing the adequacy of the data to determine whether the data is uniform can represent all thedata available with the provisions of N   N.If the test result data is uniform and meets the adequacy of the data, performed data sorting sizes from small to the largest percentile calculations and used P5, P50and P95 with a normal distribution method is to approach the average value using a 5% level of accuracy and level of 95% confidence.Based on the data obtained from the calculation can be done designing Helicopter pilot seat types Sykorski S-76 that meets the principles of ergonomics.